Czech and Polish understanding of democracy - Pająk-Patkowska, Beata; Pospíšilová, Jaroslava (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2018)
The paper attempts to analyze the results of the European Social Survey Round 6 (2012, 2013), focusing on the section related to how democracy is understood in Poland and in the Czech Republic. The most interesting issue encompassed the differences in how democracy is defined in the two countries and the outcomes these differences produce in terms of the perceived legitimacy of the system, as well as demographic factors that correlate with differences in the understanding of democracy in both surveyed groups. Statistical analyses carried out in the paper indicated the presence of different definitions of democracy formulated in Poland and in the Czech Republic (the Czechs gave stronger emphasis to the liberal aspect of democracy, whereas Poles stressed its social aspects more). Nevertheless, the relationship between the definition of democracy and the perceived level of legitimacy of the democratic system (for dispersed and specific legitimacy alike) were found to be relatively weak, as was the case of the relationship between the understanding of democracy, system legitimacy and sociodemographic factors. The only factor found to be significant for the perceived level of legitimacy of the democratic system concerned the level of satisfaction with one’s own material situation.

Celem artykułu była analiza wyników badań przeprowadzonych w ramach Euro¬pean Social Survey Round 6 (2012, 2013) w części dotyczącej rozumienia demokracji w Polsce oraz w Czechach. Interesowały nas różnice w definiowaniu demokracji występujące pomiędzy obu krajami oraz ich konsekwencje dla legitymizacji systemu, a także czynniki demograficzne różnicujące sposób rozumienia demokracji w obrębie obu badanych grup. Zastosowane analizy statystyczne wykazały istnienie różnic w definiowaniu demokracji pomiędzy Polską a Czechami (Czesi mocniej podkreślali liberalne aspekty demokracji, natomiast Polacy - socjalne). Jednak zaobserwowane relacje pomiędzy sposobem definiowania demokracji a poziomem legitymizacji systemu demokratycznego w obu wymiarach (dispersed and specific legitimacy) okazały się stosunkowo słabe. Podobnie jak zależności pomiędzy sposobem rozumienia demokracji i legitymizacji systemu demokratycznego a czynnikami społeczno-demograficznymi. Jedynie poziom zadowolenia z własnej sytuacji materialnej badanego okazał się czynnikiem istotnym dla poziomu legitymizacji systemu demokratycznego.
Czeskie i polskie rozumienie demokracji Streszczenie
Keywords: understanding of democracy; Poland; Czech Republic; rozumienie demokracji; demokracja; Polska; Czechy